Regeneration of trees in the treeline ecotone: northern Finnish Lapland - Holtmeier, Friedrich-Karl; Broll, Gabriele; Müterthies, Andreas; Anschlag, Kerstin (Geographical Society of Finland, 2003)
The objective of our research was to find out if forest will invade the treeless areas in the present treeline ecotone in northern Finnish Lapland and which factors might impede forest advance. The field studies were carried out on Ailakkavaara near Kilpisjärvi, in the Pallastunturi area, and in northern Utsjoki(Rodjanoaivi, Koahppeloaivi-Staloskaidi, Jesnalvaara). In the Kilpisjärvi area and in northern Utsjoki only mountain birch is represented in the treeline ecotone, except for Jesnalvaara, where pine also occurs. In the Pallastunturi area, mountain birch, pine and spruce are represented in the treeline ecotone up to the treeline. In all study areas, a mosaic of widely scattered trees, tree groves and almost treeless subarctic dwarf shrub-lichen heath characterize the treeline ecotone. This mosaic is closely related to the locally varying topography and its influence on site conditions. In all the places, adverse physical and biological factors impede the forest from invading the present treeless areas within the treeline ecotone. Generally, seedlings are rare on top of wind-swept convex topography compared to better wind-protected snow-rich depressions such as little stream sides. Low or missing winter snow cover, ice particle abrasion, sand blast, and reindeer cause damage to seedlings and sparse young growth. Sandy till, typical of the ecotone on Rodjanoaivi, Koahppeloaivi and Staloskaidi (northern Utsjoki), is highly susceptible to wind erosion once the protecting plant cover has been destroyed. Thus, on the prevailing convex, wind-exposed topography, frequented by reindeer, the topsoil is eroded leaving the bare mineral soil exposed. Due to the sandy texture and lack of organic matter these sites drain rapidly. Drought and poor nutrient supply are most adverse to seedling establishment. In the other study areas (Ailakkavaara, Pallastunturi and also Jesnalvaara in northern Utsjoki) wind erosion is far less important. Seedlings are more frequent in wind-sheltered, snow-rich and moist shallow valleys and ...